Correlation between Suppression of Tumorigenicity-2 with Left Ventricular Geometry, Left Ventricular Ejection Fraction and Quality of Life in Systolic Heart Failure Patients - Johan Gunadi; Starry Homenta Rampengan; Janry Antonius Pangemanan; Agnes Lucia Panda; Nancy Lampus; Hasjim Hasbullah (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Heart failure (HF) is a clinical syndrome caused by structural or functional cardiac disorders and is the final stage of every heart disease, marked by decreased functional capacity and patients’ quality of life (QoL). Suppression of tumorigenicity-2 (ST2) is a biomarker depicting heart fibrosis and remodeling that altered left ventricular geometry, which in turn decreases left ventricular contractility, decreases functional capacity, and ultimately affects the QoL of the HF patient.METHODS: An observational study was conducted with a cross-sectional approach involving 60 patients with systolic heart failure. Left ventricular geometry, left ventricular ejection fraction (LVEF), ST2 level, and other biomarkers were examined, continued by QoL assessment.RESULTS: The ST2 level (33.25±23.55 ng/mL) was negatively correlated with LVEF (r=-0.257; p=0.024) and was positively correlated with QoL (r=0.255; p=0.05). The LVEF was negatively correlated with QoL (r=-0.224; p=0.031). However, no significant correlation was found between left ventricular geometry with ST2 level or patients’ QoL.CONCLUSION: Elevated ST2 levels are correlated with decreased LVEF and worse QoL in systolic heart failure subjects. Therefore, ST2 together with LVEF can be used as prognostic tools for patients with HF.KEYWORDS: heart failure, ST2, left ventricular geometry, left ventricular ejection fraction, quality of life